2019
DOI: 10.1186/s13014-019-1342-9
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET parameters predict for recurrence in anal cancer – results from a prospective, multicentre clinical trial

Abstract: Background To investigate the prognostic significance of positron emission tomography (PET) parameters from F-18 fluorodeoxyglucose (FDG) PET scans performed pre- and post- chemo-radiotherapy (CRT) for squamous cell carcinoma of the anal canal (AC). Methods From January 2013 to January 2017, 19 patients with non-metastatic AC enrolled on a prospective trial underwent FDG-PET/CT imaging before and 12 weeks following CRT. A computer-generated volume of interest (VOI) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 28 publications
0
32
0
1
Order By: Relevance
“…Another retrospective study including 75 patients found a correlation of the MTV of the primary tumor and OS with a cut off value of 7 cm [3]. There was no significant correlation of SUV max with OS or PFS of the patients [28]. Another study that included data of 19 patients derived from a prospective multi-center trial found a correlation between the MTV on pretreatment PET/CT and any tumor recurrence in anal cancer patients treated with radiochemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study including 75 patients found a correlation of the MTV of the primary tumor and OS with a cut off value of 7 cm [3]. There was no significant correlation of SUV max with OS or PFS of the patients [28]. Another study that included data of 19 patients derived from a prospective multi-center trial found a correlation between the MTV on pretreatment PET/CT and any tumor recurrence in anal cancer patients treated with radiochemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In one report, the higher pre-treatment SUVmax was associated with poorer DFS [ 29 ]. On the other hand, several other studies failed to demonstrate a relation between SUVmax of the tumor and survival parameters [ 26 , 27 , 30 , 40 ]. In line with their findings, our results showed that higher tumor SUVmax on the pre-treatment 2-[18F]FDG PET/CT did not predict worse DFS ( p = 0.127).…”
Section: Discussionmentioning
confidence: 99%
“…Gauthé et al revealed that MTV of the pre-treatment 2-[18F]FDG PET/CT is significantly correlated with OS [ 43 ]. Jones et al claimed that the only parameter predicting any recurrence was MTV of 41% maximum SUV on the pre-treatment 2-[18F]FDG PET/CT [ 40 ]. Also, Leccisotti et al documented that higher pre-treatment MTV and TLG are correlated with poorer different survival parameters [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exact logistic regression and ROC AUC analyses were completed. Two PET-CT parameters were found to be associated with recurrence: MTV bounded by a threshold of 41% maximum SUV on the pre-CRT PET-CT predicted for any recurrence (p = 0.03, ROC AUC 0.89), and median SUV within a VOI bounded by an SUV of three on post-CRT PET-CT correlated with local recurrence (p < 0.01, ROC AUC 1.00 with a median SUV threshold of 3.38) [34].…”
Section: Pet-ctmentioning
confidence: 99%